Bufothionine induces autophagy in H22 hepatoma-bearing mice by inhibiting JAK2/STAT3 pathway, a possible anti-cancer mechanism of cinobufacini. (24th April 2021) - Kong, Wei-Song; Shen, Fang-Xue; Xie, Rui-Fang; Zhou, Gui; Feng, Yi-Ming; Zhou, Xin
Abstract: Ethnopharmacological relevance: Cinobufacini is extracted from the skins and parotid venom glands of the toad for treating symptoms like swelling and pain in ancient times. Nowadays, cinobifucini injection has also achieved satisfactory therapeutic effects on hepatocellular carcinoma (HCC) in China. Aim of the study: Our previous work found that bufothionine, an alkaloid abundant in cinobufacini injection, induced mitochondria-mediated apoptosis. In this work, the underlying effects of bufothionine on autophagy in HCC and its possible dependent pathway were investigated. Methods: CCK-8 and Hoechst staining assays were performed to verify effects of drugs on proliferation and apoptosis of SMMC7721 cell. H22 -tumor-bearing mice model was established by inoculating ascites fluid. HE staining was used to observe pathological changes in liver and tumor tissues. ELISA and Western blot experiments were conducted to investigate IL-6/JAK2/STAT3 signaling pathway. The effects of drugs on expressions of autophagic relative proteins were investigated by Western blot in vitro and in vivo . Results: In vitro, CCK-8 and Hoechst staining assays showed that bufothionine inhibited SMMC7721 cell proliferation and promoted apoptosis at 100 μM. In vivo, bufothionine relieved symptoms of H22 -tumor-bearing mice and exerted anti-inflammation activity. ELISA and Western blot demonstrated that bufothionine significantly reduced serum IL-6 concentration, suppressed p -Stat3tyr705, p -Stat3ser727 and Jak2 expressions in tumor tissues and upregulated Atg5, Atg7 and LC3Ⅱ expressions in SMMC7721 cell and H22 tumor. Conclusion: This is the first report showing that bufothionine might induce autophagy in HCC by inhibiting JAK2/STAT3 pathway, presenting a possible anti-cancer mechanism of bufothionine in cinobufacini injection. Graphical abstract: Image 1